Key miRNAs and Genes in the High-Altitude Adaptation of Tibetan Chickens - Chen, Binlong; Li, Diyan; Ran, Bo; Zhang, Pu; Wang, Tao (Frontiers in Veterinary Science, 2022)
Tibetan chickens living at high altitudes show specific physiological adaptations to the extreme environmental conditions. However, the regulated base of how chickens adapt to high-altitude habitats remains largely unknown. In this study, we sequenced 96 transcriptomes (including 48 miRNA and 48 mRNA transcriptomes of heart, liver, lung, and brain) and resequenced 12 whole genomes of Tibetan chickens and Peng'xian yellow chickens. We found that several miRNAs show the locally optimal plastic changes that occurred in miRNAs of chickens, such as miR-10c-5p, miR-144-3p, miR-3536, and miR-499-5p. These miRNAs could have effects on early adaption to the high-altitude environment of chickens. In addition, the genes under selection between Tibetan chickens and Peng'xian yellow chickens were mainly related to oxygen transport and oxidative stress. The I-kappa B kinase/NF-kappa B signaling pathway is widely found for high-altitude adaptation in Tibetan chickens. The candidate differentially expressed miRNAs and selected genes identified in this study may be useful in current breeding efforts to develop improved breeds for the highlands.